Causal associations between dietary antioxidant vitamin intake and lung cancer: A Mendelian randomization study - Zhao, Hang; Jin, Xiaolin (Frontiers in Nutrition, 2022)
Background Oxidative stress is currently considered to be closely related to the occurrence of respiratory tumors, especially lung cancer. Many observational studies have shown that increased antioxidant intake can reduce the risk of lung cancer, but the results are still controversial. Therefore, we performed a two-sample Mendelian randomized (MR) analysis to clarify the causal relationship between antioxidant vitamins and lung cancer. Methods To assess the causal effect of dietary antioxidant vitamin intake on lung cancer, we conducted a two-sample MR analysis and we extracted single-nucleotide polymorphisms (SNPs) that are associated with antioxidants from genome-wide association studies (GWASs) of the UK biobank. We gathered summary data for lung cancer from the International Lung Cancer Consortium (ILCCO), including 11,348 cases and 15,861 controls, and applied the inverse-variance weighted (IVW) method as the primary MR analysis, and performed a sensitivity analysis to verify the results. Results The results showed that higher dietary retinol intake was causally associated with lung cancer overall [odds ratio (OR) = 1.844, 95% CI, 1.359–2.502, p = 0.00009], squamous cell lung cancer (OR = 2.162, 95% CI, 1.117–4.183, p = 0.022), and lung adenocarcinoma (OR = 1.706, 95% CI, 1.084–2.685, p = 0.021). Additionally, carotene was positively correlated with lung adenocarcinoma (OR = 1.510, 95% CI, 1.002–2.276, p = 0.049). However, there was a non-significant relationship between the intake of other dietary antioxidants (vitamin C and vitamin E) and lung cancer. Conclusion Our research showed that dietary retinol intake has an adverse impact on lung cancer, and carotene might increase the risk of adenocarcinoma. This highlights the importance of revealing the underlying mechanisms of dietary antioxidant vitamins in lung cancer and delivers an important health message that dietary antioxidant vitamin intake may not be necessary for the prevention of lung cancer. It also provides a basis for future research.